Flight initiation distance is repeatable and geographically flexible in greylag geese Anser anser - Andrew C. Katsis; Lauren K. Common; Jonas Lesigang; Avila Bold; Marie Fröhlich; Jana-Marie Schmincke; Didone Frigerio; Sonia Kleindorfer (Journal of Avian Biology, 2025)
The decision to flee from an approaching threat represents a trade‐off between the costs and benefits of flight. In research to date, particular interest has been given to the effects of urbanisation on predator escape behaviour. However, these differences are most often studied at the population rather than individual level, which makes it difficult to disentangle whether site‐specific differences in predator avoidance are due to behavioural plasticity or non‐random distribution of behavioural phenotypes. In this study, we measured flight initiation distances – a widely used proxy for fearfulness or boldness – in a free‐roaming, human‐habituated, and colour‐banded population of greylag geese Anser anser. First, we tested whether individuals flexibly adjusted their flight initiation distance based on environmental context by approaching the same individuals at two sites with different levels of human presence. Second, we examined whether flock members show consistent differences in their flight initiation distance towards unfamiliar humans. Our results suggest that greylag geese can adjust their behaviour based on environmental context and show individual differences in flight initiation distance that are consistent both within and across years. When individuals regularly move between foraging sites, establishing site‐specific responses to potential threats may allow them to optimise their escape response and thereby avoid unnecessary energetic and opportunity costs. Keywords: Anser anser, behavioural plasticity, boldness, escape behaviour, flight initiation distance